Putusan Positive Legislature pada Mahkamah Konstitusi dan Implikasinya terhadap Asas Erga Omnes Praktik Rangkap Jabatan yang Dilakukan Wakil Menteri - Adelia Rahmawati Putri; Anajeng Esri Edhi Mahanani (Yustisia Tirtayasa: Jurnal Tugas Akhir, 2022)
The Constitutional Court is an institution that has exercised judicial review since the third amendment of the 1945 Constitution as the guardian of the constitution that in charge to cancel norms (negative legislation) in-laws and regulations that are considered contrary to the 1945 Constitution of the Republic of Indonesia as the highest constitution. However, several legal products whos created by the legislature did not create a complete arrangement so that it became a gap in the existence of a legal vacuum and prompted the Constitutional Court to not only cancel norms but also to formulate new norms that were regulating (positive legislation). The principle of erga omnes which is attached to every decision of the Constitutional Court also indicates that every decision of the Constitutional Court must be obeyed by all parties, including state institutions whose interests are in conflict with the 1945 Constitution of the Republic of Indonesia. The addition of new norms that regulate the Constitutional Court Decision Number 80/PUU-XVII/2019 concerning The prohibition on concurrent positions by the Deputy Minister has not been complied with and it was found that the practice of concurrent positions of deputy ministers in 2020. This indicates that the positive legislative decision with the application of the erga omnes principle still does not have firm legal force because the decision of the Constitutional Court is still considered as a recommendation. This study will answer the authority of the Constitutional Court in issuing decisions from negative legislation to positive legislation and the implications of the erga omnes principle on positive legislative decisions which provide a new norm that deputy ministers are prohibited from holding concurrent positions. This research uses the juridical-normative method by using library research. The results show that the addition of a new norm to the decision of the Constitutional Court is an act of judges in finding the law (rechtvinding) and its implications for the principle of erga omnes for rulings that have a regulatory nature have been repaired although it takes a long time.